2020
DOI: 10.25259/sni_736_2020
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and work-life balance in neurosurgery: Current state and opportunities

Abstract: Background: Burnout is a syndrome characterized by emotional exhaustion, depersonalization, and reduced sense of personal accomplishment. The syndrome has been recognized as a pandemic among physicians. The demanding nature of neurosurgery makes neurosurgeons, particularly prone to burnout. In recent years, pioneering work has shed light on burnout in the field of neurosurgery. Methods: We have reviewed the literature in PUBMED on burnout in physicians, focusing on neurosurgical publications. Results: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
(35 reference statements)
0
7
0
1
Order By: Relevance
“…More weekly calls have been considered a contributing factor to burnout in residents, and similar would be expected in neurosurgery consultants [ 9 ]. However, our study observed the consultants with burnout to have a lower mean of weekly calls, which is an unexpected finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More weekly calls have been considered a contributing factor to burnout in residents, and similar would be expected in neurosurgery consultants [ 9 ]. However, our study observed the consultants with burnout to have a lower mean of weekly calls, which is an unexpected finding.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgical healthcare workers can also be at risk of high burnout, attributed to their mental and physical demands and the extended training duration [ 9 ]. The literature reports burnout to be widely present in neurosurgeons [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Los participantes en nuestro estudio informaron que las dificultades más comunes en la neurocirugía son la naturaleza desafiante y compleja de los casos neuroquirúrgicos, aunado al largo período de formación en posgrado y porque consideraron que la neurocirugía podría afectar su vida familiar y social, al ser una especialidad muy demandante. Los cuadros clínicos de rápida instauración, la posibilidad de complicaciones devastadoras en los pacientes y las implicaciones médico legales en los pacientes neuroquirúrgicos hacen que la neurocirugía tenga una considerable predisposición al síndrome del Burnout 25 . Además, la neurocirugía se ha relacionado con el aumento en los índices de divorcio, relaciones sentimentales fallidas y conflictos familiares 26 .…”
Section: Discussionunclassified
“…Programs may explore their residents' preferences, engage them in planning, emphasize balance, and cultivate a culture of support for prioritizing wellness. 31,52 Although burnout/wellness interventions have previously been described in excellent reviews, [53][54][55] we found it important to contextualize these interventions within the rest the published neurosurgical educational intervention literature. Being the third most prominent field signifies the perceived importance of reducing resident burnout.…”
Section: Wellness and Burnoutmentioning
confidence: 96%